Parents' Views on Play and the Goal of Early Childhood Education in Relation to Children's Home Activity and Executive Functions: A Cross-Cultural Investigation - Metaferia, Biruk K.; Futo, Judit; Takacs, Zsofia K. (Frontiers in Psychology, 2021)
The present study investigated the cross-cultural variations in parents’ views on the role of play in child development and the primary purpose of preschool education from Ethiopia and Hungary. It also examined the cross-cultural variations in preschoolers’ executive functions (EF), the frequency of their engagement in home activities, and the role of these activities in the development of EF skills. Participants included 266 preschoolers (Ethiopia: 62 boys; Mage = 63.83 months; SD = 7.68 months; Hungary: 61 boys; Mage = 62.06 months; SD = 9.37 months) with their parents (Ethiopia: 63 male; Mage = 36.66 years; SD = 7.14 years; Hungary:17 male; Mage =37.71 years; SD = 5.97 years). The independent samples t-test showed that Ethiopian parents view fostering academic skills for preschooler significantly more important than their Hungarian counterparts do. We also found that while Ethiopian parents hold the belief that academic and cognitive development is the major purpose of preschool education, Hungarian prioritize social-emotional development and entertainment. Additionally, preschoolers in Ethiopia were reported to engage in academic and arts and crafts activities after preschool significantly more frequently than their Hungarian counterparts. On the contrary, preschoolers in Hungary were found to engage in fine-motor activities, solitary play, sports and other physical activities significantly more frequently than their Ethiopian counterparts. No significant differences were found in EF skills between preschoolers from Ethiopia and Hungary. Results from hierarchical regression analyses showed that, after accounting for age and SES, preschoolers’ frequency of pretend play and their parents’ play support beliefs were found to be small to medium-sized predictors of inhibitory control skills in both samples. However, children’s frequency of having breakfast at home was another significant predictor in the Ethiopian sample only. The frequency of participation in arts and crafts and other fine-motor activities were found to be important predictors of preschoolers’ visual-spatial working memory skills in the Ethiopian and the Hungarian samples respectively. We also found that, after controlling for SES, parental play support was an important factor associated with preschoolers’ shifting skills only in the Hungarian sample. Based on the findings, we made important conclusions.